Visual Learning Meets Dual Coding: Rethinking Arabic Reading Pedagogy - Vivia Salma Azzaahro; Ikhwanul Habib; Taqiyuddin Kabalmay; Muhibbuddin Muhibbuddin (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2026)
The main problem of this research is the low optimization of students' reading skills (maharah qiroah) due to the dominance of conventional methods, so it is necessary to implement an Image-Based Learning approach based on Dual Coding theory. This study aims to analyse the implementation of the Image-Based Learning (IBL) approach based on the Dual Coding theory in improving Arabic reading skills (maharah qiroah) of 12 postgraduate students during the learning process in the classroom. The study employs a descriptive qualitative method, with data collected through direct observation, in-depth interviews, and documentation of the learning process in the Arabic Language Education Programme at UIN Maulana Malik Ibrahim Malang. Data validity is ensured through triangulation of sources and data collection techniques. The results indicate that the IBL approach is effective in activating students' schemas, enriching vocabulary, deepening understanding of Arab cultural context, and developing critical thinking skills through text structure analysis. The integration of Dual Coding theory enables students to process information simultaneously through visual and verbal channels, significantly enhancing retention and reading comprehension. These findings reinforce the evidence of the effectiveness of interactive visual media in Arabic language learning. The contribution of this research lies in affirming the strategic role of visualisation in developing analytical skills and comprehensive discourse understanding. Therefore, the Dual Coding-based IBL approach is recommended as an adaptive pedagogical strategy in maharah qirā’ah learning to meet the demands of 21st-century learning.